2022
DOI: 10.1111/nyas.14761
|View full text |Cite
|
Sign up to set email alerts
|

Testing the specificity of links between anxiety and performance within mathematics and spatial reasoning

Abstract: Anxiety within the domains of math and spatial reasoning have consistently been shown to predict performance within those domains. However, little work has focused on how specific these associations are. Across two studies, we systematically tested the degree of specificity in relations between anxiety and performance within math and spatial reasoning. Results consistently showed that anxiety within a cognitive domain predicted performance in that domain even when controlling for other forms of anxiety, provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…And while the present work focused specifically on links between cognition-specific anxieties and avoidance tendencies, we believe the idea behind this framework could be extended to better understand links between anxiety and performance within specific cognitive domains as well. While it is well-documented that those who are anxious about specific types of thinking underperform on tasks that involve the relevant type of thinking 1 , 3 , 4 , 6 , 31 , future work could address whether these associations are dependent on individual perceptions of how much a given task involved the type of thinking in question. To use the spatial domain as an example, some people may believe that a computer programming task involves a lot of spatial reasoning while others may believe it involves relatively little.…”
Section: Discussionmentioning
confidence: 99%
“…And while the present work focused specifically on links between cognition-specific anxieties and avoidance tendencies, we believe the idea behind this framework could be extended to better understand links between anxiety and performance within specific cognitive domains as well. While it is well-documented that those who are anxious about specific types of thinking underperform on tasks that involve the relevant type of thinking 1 , 3 , 4 , 6 , 31 , future work could address whether these associations are dependent on individual perceptions of how much a given task involved the type of thinking in question. To use the spatial domain as an example, some people may believe that a computer programming task involves a lot of spatial reasoning while others may believe it involves relatively little.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, whether gender differences in spatial selfconcept exist in childhood is an open question. Critically, emerging work supports the potential that math and spatial anxieties are unique but contribute to cross-domain outcomes (Daker et al, 2022;Delage et al, 2021;Sokolowski et al, 2019). For example, recent work has found an explanatory role of spatial anxiety for gender differences in math anxiety in adulthood (Delage et al, 2021;Sokolowski et al, 2019), highlighting the importance of studying math and spatial attitudes concurrently.…”
Section: Spatial Attitudesmentioning
confidence: 94%
“…Recent work has suggested that spatial attitudes may also be relevant for STEM success (Daker et al, 2022; Delage et al, 2021; Sokolowski et al, 2019). As expected, the handful of studies investigating spatial anxiety have revealed negative relations between spatial anxiety and performance on spatial tasks such as mental rotation, both in adults and elementary-school-aged children (Alvarez-Vargas et al, 2020; Lauer et al, 2018; Ramirez et al, 2012).…”
Section: Math and Spatial Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, few researchers investigated the relationship between chemistry anxiety, chemistry identity, and chemistry career choices. Research on understanding the relationship between anxiety, identity, and career choices is mostly in math fields, while these variables are domain-specific (Hosbein and Barbera, 2020;Daker et al, 2022). Secondly, previous studies examined identity and anxiety as unidimensional variables (Huang et al, 2018;Cribbs et al, 2021).…”
Section: Methodsmentioning
confidence: 99%